Driver of discontent or escape vehicle: the affective consequences of mindwandering - Mason, Malia; Brown, Kevin; Mar, Raymond A.; Smallwood, Jonathan (Frontiers in Psychology, 2013)
An emerging body of evidence suggests that our penchant for entertaining thoughts that are unrelated to ongoing activities might be a detriment to our emotional wellbeing. In light of this evidence, researchers have posited that mindwandering is a cause rather than a manifestation of discontent. We review the evidence in support of this viewpoint. We then consider this evidence in a broader context – with regards to mindwandering’s antecedents, respecting the observation that people frequently find pleasure in their off-task moments, and in light of the lay beliefs people hold about its causes. We report data from two studies that speak to the potential challenges of establishing a definitive causal link between mindwandering and wellbeing. First, to advance the idea that mindwandering can convey affective benefits, in spite of negative feelings about mental disengagement, we examined cortical responses in a unique individual who presents with a long history of excessive—but enjoyable—task-irrelevant thinking. Second, to explore the idea that lay beliefs about mindwandering may substantially color the affective responses people have to a mindwandering episode, we surveyed people’s beliefs about mindwandering’s antecedents and related them to the affective reactions people anticipated to off-task moments. Our hope is to provide a nuanced evaluation of the available evidence for the assertion that mindwandering causes unhappiness, and to provide a clear direction forward to better evaluate this possibility.